Accessibility and usability of Online Labs: real barriers in a virtual world - Joaquim Faias (2007)
This paper was produced under the framework of the Labs-on-the-web project, funded by the Portuguese Ministry of Science, Technology and Higher Education, within the scope of the Science and Innovation Operational Program (POCI 2010). We intended to verify if the online access to the workbenches designed with the NI LabVIEW platform was respecting the accessibility and usability standards, so that students with disabilities could benefit from this emerging pedagogical tool. We found out that the virtual workbenches build under this project had several errors that compromise the use of this technology by students with special needs, expressly by those with visual impairments.